Influence of Feeding Albizia lebbeck and Terminalia arjuna Leaves on Growth Performance and Nutrient Utilization in Surti Kids - Patel, V.R.; Choubey, M.; Raval, A.P.; Desai, M.C. (Indian Journal of Animal Nutrition, 2018)
Thirty growing Surti kids were divided into five treatments of six animals each to evaluate the effects of feeding Albizia lebbeck (AL) and Terminalia arjuna (TA) leaves on growth performance and nutrient utilization. The kids in treatment T1 (control) were fed with basal diet containing 200 g of green jowar which was replaced with AL leaves (T2), TA leaves (T2) or equal mixture of AL and TA leaves in treatment T4 (200 g) and T5 (300 g). The nutrient intake was not affected by feeding of tree leaves. Digestibility of all the nutrients and fibre fractions were higher (P